Static and dynamic impairment following stroke reflecting hemispheric asymmetry for postural control - Suellen Marinho Andrade; Bernardino Fernandéz-Calvo (Universidade Estadual de Maringá, 2015)
This paper evaluates whether there is a relationship between postural control and hemispheric asymmetry following a stroke. Twenty right or left brain-damage patients and ten healthy control subjects were included in this study. The static (weight symmetry) and dynamic posture (velocity, maximal excursion and the directional control of the center of mass) were analyzed by quantitative posturography. Factors such as clinical neurological assessment, postural skills, muscle strength, spasticity, sensitivity and hemineglect were also collected. Results showed that in static posture, right-brain-damaged patients had worse performance. In the dynamic tests, left-brain-damaged patients were selectively impaired on maximal excursion and the directional control of the center of mass, while right-brain-damaged patients were more impaired on movement velocity. The results show specific mechanisms for modulating posture depending on the damaged side. These findings support the idea that each hemisphere contributes differently to static and dynamic postural control.